Nano-fertilizer -Way towards Efficient Crop Nutrition - Saha, Soumya; Verma, Bibhash Chandra; Sow, Prodipto; Bhaduri, Debarati; Prasad, Shiv Mangal (Chronicle of Bioresource Management, 2023)
Nano fertilizers have emerged as a potential solution to the challenges associated with traditional synthetic fertilizers in agriculture. Nano-fertilizer offers advancements in crop management systems by improving nutrient delivery and reducing the reliance on synthetic fertilizers. They can be categorized as nanoscale fertilizers, nanoscale additive fertilizers, or nanoscale coating fertilizers, depending on their composition and mode of action. Nanomaterials encapsulate nutrients and enable slow and efficient nutrient release, resulting in balanced nutrition throughout the plant’s growth cycle. Nano fertilizers offer advantages such as increased crop yield, enhanced nutrient availability, and reduced adverse environmental impact. However, careful monitoring and advance research are necessary to address limitations and ensure safe and effective use. Future studies should focus on evaluating the safety and toxicity of nanomaterials, understanding their interaction with different soil types, exploring bio-synthesized nanoparticle-based fertilizers, and assessing their impact on the environment and human health.